Education, Work and Social Change - Simmons, R. author. aut Link
X, 257 p.
Keywords: Drawing on a longitudinal study of the lives of NEET young people, this book looks beyond dominant discourses on youth unemployment to provide a rich, detailed account of young people's experiences of participation and non-participation on the margins of education and employment, highlighting the policy implications of this research.